Alzheimer's Disease and Chinese Medicine as a Useful Alternative Intervention Tool: A Mini-Review - Klimova, Blanka; Kuca, Kamil (Current Alzheimer research, 2017)
BACKGROUND: Alzheimer´s disease (AD) is a serious and complex neurodegenerative disease. Currently, there are about 44 million people suffering from AD all over the world and this number is expected to rapidly grow due to demographic changes. The disease can be treated both pharmacologically and non-pharmacologically. Unfortunately, it cannot be cured yet. Nevertheless, the drugs for the treatment of AD are quite expensive, have different side effects and only delay symptoms of this disease. Therefore researchers suggest the use of various non-pharmacological therapies. Apart from relatively popular in western world such as physical activities, cognitive training or healthy diet, Chinese medicine starts to be practiced in Europe. OBJECTIVE: The purpose of this mini-review is to discuss the concept of Chinese medicine and explore its most common and effective forms in the treatment of AD. METHODS: This was done by conducting a literature search in the world´s acknowledged databases such as Web of Science, Scopus, PubMed and Springer. RESULTS: Five randomized controlled clinical trial studies were analyzed and their findings were discussed. CONCLUSION: The authors of this mini-review list the key benefits (e.g., positive results of the reviewed randomized clinical trials studies for the improvement of cognitive decline in AD) and limitations (e.g., low awareness of benefits of TCM in Europe) of Chinese medicine therapy for the treatment of AD.
Keywords: Alzheimer's disease; findings; databáze bibliografické; léky rostlinné čínské; Alzheimer Disease; Databases, Bibliographic; limitations; zvířata; Humans; Randomized Controlled Trials as Topic; tradiční čínská medicína; Medicine, Chinese Traditional; Alzheimerova nemoc; randomizované kontrolované studie jako téma; Chinese medicine; benefits; Drugs, Chinese Herbal; lidé; concept; Animals